Labor Dystocia and the Risk of Uterine Rupture in Women with Prior Cesarean - Vachon-Marceau, Chantale; Demers, Suzanne; Goyet, Martine; Gauthier, Robert; Roberge, Stéphanie; Chaillet, Nils; Laroche, Jasmin; Bujold, Emmanuel (American Journal of Perinatology, 2016)
Objective The objective of this study was to evaluate the association between labor dystocia and uterine rupture.Methods We performed a secondary analysis of a multicenter case–control study that included women with single, prior, low-transverse cesarean section who experienced complete uterine rupture during a trial of labor (TOL). For each case, three women who underwent a TOL without uterine rupture were selected as controls. Data were collected on cervical dilatations from admission to delivery. We evaluated the relationship between uterine rupture and labor dystocia according to several criteria, including the World Health Organization's (WHO's) partogram.Results Data were available for 90 cases and 260 controls. Compared with the controls, uterine rupture was associated with less cervical dilatation on admission, slower cervical dilatation in the first stage of labor and longer second stage of labor (all with p < 0.05). Performing cesarean when the labor curve crossed the ACTION line of WHO's partogram or when the second stage was greater than 2 hours could have (1) prevented up to 56% of uterine rupture and (2) reduced the duration of labor in 57% of women with failed TOL.Conclusion Labor dystocia is a significant risk factor for uterine rupture. Labor progression should be assessed regularly in women with prior cesarean.
Keywords: pregnancy; cesarean; vaginal birth after cesarean; uterine rupture; labor dystocia